Antimicrobial stewardship - Laundy, Matthew; Gilchrist, Mark; Whitney, Laura (Oxford University Press, 2016)
Antibiotic resistance threatens the effective prevention and treatment of infections. Antimicrobial Stewardship provides a practical guide on this growing area, supported by the review of the available evidence, including example case studies.